Establishment Success of the Beetle Tapeworm Hymenolepis diminuta Depends on Dose and Host Body Condition - Dhakal, Suraj (Insects, 2018)
Parasite effects on host fitness and immunology are often intensity-dependent. Unfortunately, only few experimental studies on insect-parasite interactions attempt to control the level of infection, which may contribute substantial variation to the fitness or immunological parameters of interest. The tapeworm Hymenolepis diminuta—flour beetle Tenebrio molitor model—has been used extensively for ecological and evolutionary host–parasite studies. Successful establishment of H. diminuta cysticercoids in T. molitor relies on ingestion of viable eggs and penetration of the gut wall by the onchosphere. Like in other insect models, there is a lack of standardization of the infection load of cysticercoids in beetles. The aims of this study were to: (1) quantify the relationship between exposure dose and establishment success across several H. diminuta egg concentrations; and (2) test parasite establishment in beetles while experimentally manipulating host body condition and potential immune response to infection. Different egg concentrations of H. diminuta isolated from infected rat feces were fed to individual beetles 7–10 days after eclosion and beetles were exposed to starvation, wounding, or insertion of a nylon filament one hour prior to infection. We found that the establishment of cysticercoids in relation to exposure dose could be accurately predicted using a power function where establishment success was low at three lowest doses and higher at the two highest doses tested. Long-term starvation had a negative effect on cysticercoid establishment success, while insertion of a nylon filament and wounding the beetles did not have any effect compared to control treatment. Thus, our results show that parasite load may be predicted from the exposure dose within the observed range, and that the relationship between dose and parasite establishment success is able to withstand some changes in host body condition.